Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 34. Beitrag. Lepidoptera: Hesperiidae. - Alberti, Burchard (Contributions to Entomology = Beiträge zur Entomologie, 1965)
The Hesperiidae collected in the expedition to Albania by Deutsches Entomologisches Institut (including the findings of a previous tour of Albania by Dr. Friese) total 39 specimens of 10 species. There were no new discoveries, which indicates that practically all the Hesperiidae of that country have been determined. At present 21 species of this family are known from Albania. Similar numbers of species appear in a comparative survey of other countries in the southern and central parts of the Balkan peninsula.